MOTIVATION OF FISH FARMERS IN MAKING INDEPENDENT FISH FEED IN THE VILLAGE OF KOTO TIBUN KAMPAR REGENCY RIAU PROVINCE - Simamora, Boston Tigor; Kusai, Kusai; Zulkarnain, Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis research aims to determine the factors that encourage farmers to make independent fish feed and to determine the motivation level of fish farmers in making independent fish feed in Koto Tibun Village, Kampar Regency, Riau Province. The method used is a survey method by making direct observations to the object of research by collecting data through a questionnaire, selecting respondents using a census method carried by 27 people. The data obtained were analyzed by descriptive method, using a Likert Scale. The results showed that the driving factor for farmers in making independent feed is the price of expensive factory feed, the quality of self-feed is not much different from the quality of factory feed, the cost of feed is more profitable and the increase in cultivators in Koto Tibun Village is 77.78% available in the category high (score 160-200), meaning encouraging fish farmers to make independent feed wholeheartedly to run this business.Keywords: Motivation, Fish Farmers and Independent Fish Feed